1994
DOI: 10.1093/oxfordjournals.aje.a116939
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Risk of Fatal Breast Cancer

Abstract: The authors examined the association of fatal breast cancer and cigarette smoking in a large, prospective mortality study of US adults. After 6 years of follow-up, 880 cases of fatal breast cancer were observed in a cohort of 604,412 women who were cancer-free at interview in 1982. Cox proportional hazards modeling, adjusted for other risk factors, found that current smoking was significantly related to fatal breast cancer risk (adjusted rate ratio (RR) = 1.26, 95% confidence interval (CI) 1.05-1.50). A negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 0 publications
9
60
1
1
Order By: Relevance
“…In the American Cancer Society prospective study of adult women, Calle et al found that smoking was associated with an increased risk of fatal breast cancer (RR 1.26, 95% CI = 1.05-1.50), that increased with number of cigarettes and number of years smoked [27]. Yu et al found a relative risk of death from breast cancer of 1.40 (95% CI = 1.0-1.9) associated with smoking, after adjustment for tumor characteristics and other potential confounders [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the American Cancer Society prospective study of adult women, Calle et al found that smoking was associated with an increased risk of fatal breast cancer (RR 1.26, 95% CI = 1.05-1.50), that increased with number of cigarettes and number of years smoked [27]. Yu et al found a relative risk of death from breast cancer of 1.40 (95% CI = 1.0-1.9) associated with smoking, after adjustment for tumor characteristics and other potential confounders [28].…”
Section: Discussionmentioning
confidence: 99%
“…The totals for the different variables may not equal to the total number of subjects in a category because of missing data Table 2 Prevalence of smoking among women less than 50 years of age, according to recruitment site and BRCA mutation status (23) 26 (22) 21 (33) 25 (28) 41 (27) 51 (24) Current a…”
Section: Live Births and Stillbirths Dmentioning
confidence: 99%
“…Indeed, there has been substantial interest in this area of gene-smoking-breast cancer interaction, even though studies examining this question are still mostly in progress [recently reviewed in Ambrosone, 2001]. [Hirayama, 1990] 16 1.0 1.3 (0.8-2.0) 1.6 (1.01-2.5) Wartenberg [Wartenberg et al, 2000] 12 1.0 1.0 (0.8-1.2) Calle [Calle et al, 1994] 6 1.0 1.3 a (1.05-1.5) 0.9 (0.7-1.03) Manjer [Manjer et al, 2000] 10-20 1.0 2.0 (1.2-3.1) 1.3 (0.6-2.7)…”
Section: Metabolic Susceptibilitymentioning
confidence: 99%
“…Smoking history was reported in less than 1% of our population (2/333 patients); however, it was impossible to assess the association of smoking with survival factors. Two studies found that smoking reduced the survival rate of breast cancer patients (33,34).…”
Section: Discussionmentioning
confidence: 99%